The impact of high alkali media on the biochemical compositions of two hydrophytes; Lemna minor L. and Ceratophyllum demersum L. from Shatt Al-Arab River, Basrah-Iraq - Haraib, K.K. (Mesopotamian Journal of Marine Sciences, 2022)
The present work aims at understanding the effect of high alkali media on the biochemical composition of two hydrophytes; Lemna minor L. and Ceratophyllum demersum L. Each of these two hydrophytes was planted in 4-one liter glass containers of pH 7.5, 8.5, 9.5 and 10.5 under laboratory conditions. Samples were taken after two weeks for physico-chemical parameters and tissue (protein, fat and ash) analysis. The results show that the highest protein contents (34.81 %, 34.66 %) were found in the control medium of L. minor, in C. demersum at pH 7.5. The least protein content was 21.45% in L.minor at pH 9.5. As to the fat contents the highest value (7.50 %) was recorded in L. minor at pH 9.5, while the least one was 1.181% in L. minor at pH 10.5. The highest ash content of C. demersum was 19.88 % at pH 10.5 and the least was 11.93% at the control. High pH showed negative impact on protein content of the two aquatic plants. The protein was reduced as the pH value elevates, but at pH 10.5 the protein content rised again. As for fat content, increasing pH caused increasing of fat in L. minor and its decreasing in C. demersum except pH 10.5 at which the fat comes up again in reverse to the former plant. The ash content of L. minor was fluctuating, whereas in C. denersum, the increasing of pH value caused increasing of ash content.